KRITIK ATAS PANDANGAN WILLIAM M. WATT TERHADAP SEJARAH PENULISAN AL-QUR’AN - Alwi, Muhammad (Jurnal Studi Ilmu-ilmu Al-Qur’an dan Hadis, 2020)
The study of the Qur’an has been a topic of interest to many circles, excluding Western scholars. Many of the themes they promote are generally related to the authenticity of the Qur’an. To get into this problem, many circles start arguing from the history of the Qur’an. It is this theme that William M. Watt is concerned within studying the Qur’an. Watt begins his narrative by referring to the term Ummi referred to by the Prophet Muhammad. Likewise, arguments about the literary tradition of the community are presented by reference to many verses in the Qur’an. The majority of interpretations produced are in sharp contrast to the views of the majority of Muslim scholars, so this study aims to conduct a review of Watt’s views using thematic methods. This study concludes that the Qur’anic verses used as the basis for Watt’s argument over the history of Qur’anic writing can be categorized into two types; historical arguments and interpretations. In the model of historical argument, Watt tends to assume that the writing tradition among the Arabs is also owned by the Prophet, so that the word of the people attached to the Prophet is understood as the Prophet’s ignorance of the ancient scriptures. To reinforce the historical argument, Watt analyzes several passages relating to the term public for reinterpretation. Watt’s steps in explaining the Qur’an’s writing history tend to differ from many circles. Some historical arguments using the basis of verse tend to generalize their context, thus influencing many subsequent interpretations. This is why Watt’s opinion is different from the opinion of the majority of scholars.